Cardiac electrophysiological alterations and clinical response in cardiac resynchronization therapy with a defibrillator treated patients affected by metabolic syndrome. Issue 14 (April 2017) - Sardu, Celestino; Santamaria, Matteo; Funaro, Stefania; Sacra, Cosimo; Barbieri, Michelangela; Paolisso, Pasquale; Marfella, Raffaele; Paolisso, Giuseppe; Rizzo, Maria Rosaria
Abstract : Abstract: Metabolic syndrome (MS) is a multifactorial disease that can affect clinical outcomes in patients treated by Cardiac Resynchronization Therapy with a defibrillator (CRT-d). Ninety-one patients received a CRT-d. According to clinical diagnosis, the study population was divided into 46 MS (cases) versus 45 no MS (controls) patients. These patients were followed by clinical, instrumental assessment, and device telemetric interrogations at follow-up. The design of the study was to evaluate the functionality of the CRT-d leads, the arrhythmic events, the CRT-d response, and the clinical outcomes at follow-up. At follow-up, there was a statistical significant difference, comparing MS versus no MS patients regarding the sensing, pacing, and impedance thresholds of the right atrium, right ventricle, and left ventricle leads. There was a statistically significant difference in the percentage of CRT-d responders comparing MS (n = 16, 51%) versus no MS (n = 40, 77%) patients ( P  = 0.017). MS may be predictive for hospitalization for heart failure worsening (hazard ratio 0.327, 95% confidence interval 0.096–0.943, P  = 0.044) in CRT-d patients. MS is a complex multifactorial disease that may affect the functionality of CRT-d leads, the CRT-d response, and clinical outcomes in failing heart patients. These parameters may be detectable by follow-up monitoring.